2017
DOI: 10.1002/jmri.25845
|View full text |Cite
|
Sign up to set email alerts
|

MRI proton density fat fraction is robust across the biologically plausible range of triglyceride spectra in adults with nonalcoholic steatohepatitis

Abstract: Background Proton density fat fraction (PDFF) estimation requires spectral modeling of the hepatic triglyceride (TG) signal. Deviations in the TG spectrum may occur, leading to bias in PDFF quantification. Purpose To investigate the effects of varying six-peak TG spectral models on PDFF estimation bias. Study Type Retrospective secondary analysis of prospectively acquired clinical research data. Population Forty-four adults with biopsy-confirmed nonalcoholic steatohepatitis. Field Strength/Sequence Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…38 Measurement of hepatic triglycerides content by means of magnetic resonance imaging of proton density fat fraction (MRI-PDFF) has been validated against the gold standard for non-invasive assessment, that is magnetic resonance spectroscopy. 39 MRI-PDFF measurement correlates with histologically determined steatosis both in cross-sectional and in prospective evaluation. 40 In keeping with a causal role of hepatic fat in determining liver disease progression, high MRI-PDFF has now been associated with liver fibrosis progression, independently of several metabolic confounders.…”
Section: Imag Ing S Tud Ie Smentioning
confidence: 85%
See 1 more Smart Citation
“…38 Measurement of hepatic triglycerides content by means of magnetic resonance imaging of proton density fat fraction (MRI-PDFF) has been validated against the gold standard for non-invasive assessment, that is magnetic resonance spectroscopy. 39 MRI-PDFF measurement correlates with histologically determined steatosis both in cross-sectional and in prospective evaluation. 40 In keeping with a causal role of hepatic fat in determining liver disease progression, high MRI-PDFF has now been associated with liver fibrosis progression, independently of several metabolic confounders.…”
Section: Imag Ing S Tud Ie Smentioning
confidence: 85%
“…Paralleling the advancements in the understanding of disease biology, recent technological progresses in the field of liver imaging are providing new instruments for quantification of hepatic fat content both in therapeutic trials and in the clinical practice . Measurement of hepatic triglycerides content by means of magnetic resonance imaging of proton density fat fraction (MRI‐PDFF) has been validated against the gold standard for non‐invasive assessment, that is magnetic resonance spectroscopy . MRI‐PDFF measurement correlates with histologically determined steatosis both in cross‐sectional and in prospective evaluation .…”
Section: Imaging Studiesmentioning
confidence: 99%
“…An additional limitation is that we did not examine the fat spectrum of fetal fat with MR spectroscopy (MRS), and it is possible that the fetal fat spectrum differs from the adult fat spectrum used by Quantitative CSE‐MRI, potentially introducing a source of bias in the fetal PDFF measurements. It has been shown that over the biologically possible range of multipeak fat spectral models there is minimal difference in PDFF (<2%) when compared in the livers of patients with nonalcoholic steatohepatitis . So while it is unlikely that the fetal fat spectrum is different, MRS should be used to determine the fetal fat spectrum and investigate gestational age changes and differences from the adult spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Both the pancreatic and hepatic PDFF quantification methods applied the same spectral model, which was developed for human liver triglyceride . While the human pancreatic spectral model has not yet been defined, pancreatic fat spectra derived from gas chromatography studies are similar to human liver triglyceride and prior work has shown that fat quantification estimates are insensitive to the exact spectral model …”
Section: Methodsmentioning
confidence: 99%
“…26 While the human pancreatic spectral model has not yet been defined, pancreatic fat spectra derived from gas chromatography studies are similar to human liver triglyceride 27 and prior work has shown that fat quantification estimates are insensitive to the exact spectral model. 15,28 BODY COMPOSITION QUANTIFICATION SEQUENCE. Eight overlapping image stacks were obtained from base of skull to knees.…”
Section: Pancreatic and Hepatic Pdff Sequencesmentioning
confidence: 99%